An analysis of various descriptions of state of strain in the linear Kirchhoff-Love type shell theory - LEWIŃSKI, Tomasz (Engineering Transactions, 1980)
In the first part of the paper several methods of describing the state of strain in the thin shell with Kirchhoff-Love constraints are discussed. Among others Kilchevsky's idea of the description of the state of strain in an arbitrary point of the shell is presented by means of the strain tensor parallely shifted to the base on the middle surface. Attention has been called to the physical meaning of Kilchevsky's tensor. Two forms of solving the parallel shift problem, i.e. "operator" equations and generalized Taylor series, are described and analysed. The second part of the work deals with the geometric and physical consequences of the first approximation assumption h/R